(untitled) - Labin, Suzanne (Paris, 1962)
Relations between the Soviet Union and the United States were driven by a complex interplay of ideological, political, and economic factors, which led to shifts between cautious cooperation and often bitter superpower rivalry over the years. The distinct differences in the political systems of the two countries often prevented them from reaching a mutual understanding on key policy issues and even, as in the case of the Cuban missile crisis, brought them to the brink of war.
Keywords: Hoa Kỳ,United States; Quan hệ,Relations; Liên Xô,Soviet Union